The effect of local potential-based workshop and entrepreneurship learning in increasing entrepreneurial interest - Octaverina Kecvara Pritasari; Marniati Marniati; I Wayan Susila (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2024)
This research aims to determine the effect of local potential-based workshops and entrepreneurship learning in increasing the interest in entrepreneurship of grade XI students majoring in Fashion in 3 different vocational schools in East Java Province, Indonesia. This research uses a quantitative approach. Data collection techniques were observation, questionnaires, interviews, and documentation. The population in this research was 338 students, and the sampling technique used was simple random sampling with a sample of 172 students. The data analysis technique used is descriptive statistical analysis using percentages and inferential statistical analysis techniques using data normality tests, product moment correlation analysis, and simple linear regression analysis. Based on the results of the product-moment correlation test analysis, creative product learning and entrepreneurship positively and significantly affect entrepreneurial interest in class XI students majoring in Cosmetology, amounting to 26.7 percent accepted with a low level of influence. The simple linear regression analysis results show the effect of learning creative products and entrepreneurship on student entrepreneurial interest. The results of this research are useful as input that is learning creative products and entrepreneurship based on local potential has the potential to give birth to new entrepreneurs to increase regional economic resilience.